Komnas HAM Indonesia Kedudukan dan Perannya dalam Struktur Ketatanegaraan Indonesia - Sri Hastuti Puspitasari (Jurnal Hukum IUS QUIA IUSTUM, 2002)
The need about indenpendency of National Commission for Human Rights is crucial. If wesee how ever the existence of National Commission fo Human Rights in Indonesia, the existence of Independency is very apprehensive, both juridical aspect and non-juridical. There fore, by completing the law regulation which are able to accommodafe the lack of this condition must be put into action immediately. By the expectation, the effortofconstructing the National Commission for Human Rights's task couldbe brought into reality.